Collaborative Leadership and Sustained Learner Academic Performance in Secondary Schools: A Blaming Game? - Schlebusch, Gabriel, J. (Africa Education Review Volume 17 | Number 3 | 2020 | pp. 74–89, 2020)
This article reports on a study that investigated how collaborative leadership can influence sustained learner academic performance in secondary schools. The key problem resounds about secondary schools that are unable either to sustain or improve learner academic performance when intervention strategies rolled out from the district offices are concluded. The literature pursued in the study covered collaborative leadership from both schools and district education offices and their impact on learner academic performance. Participants were circuit managers, subject advisors, principals and teachers. They completed openended questionnaires that sought to explain the relationship between collaborative leadership and sustained learner academic performance. Major findings indicated that participants (at the various levels of leadership) attribute low learner academic performance to all other involved parties except themselves. Thus, collaborative leadership within the school and between schools and district education offices is not enabling sustained learner academic performance.
Article
Keywords: Collaboration; Leadership; Academic performance; Sustainability